TL 18192 - Perspective on the Ponseti method for the treatment of clubfoot associated with amniotic band constriction syndrome - Bergamasco, Jordanna Maria Pereira; Chakkour, Marcelo; Madeiro, Raoni; Costa, Marco Tulio; Ferreira, Ricardo Cardenuto; Marchi Neto, Noé de (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Amniotic band constriction syndrome is a rare anomaly with an incidence of approximately 1:15,000 live births. It manifests as fibrous amniotic bands involving the deep fascia and, depending on its depth, can compromise the venous and lymphatic system. The presence of fibrous amniotic bands in the lower limbs is strongly associated with foot malformations, and the prevalence of clubfoot under such conditions ranges from 12 to 56%. Clubfoot associated with amniotic band constriction syndrome is characterized by rigidity and edema and tends to respond poorly to conservative treatment. We present a series of cases of clubfoot associated with amniotic band constriction syndrome that were treated with manipulation and plaster casting using the Ponseti method. Methods: Over the past 10 years, we followed 19 patients with amniotic band constriction syndrome affecting the lower limbs. Of these patients, 6 had clubfoot, including 2 who were bilaterally affected. The 6 children in this series had constriction bands in Hennigan and Kuo zone 2. The 8 affected feet were rigid, with a mean Pirani score of 5.5 and Dimeglio III classification. Four extremities with complete constriction bands initially underwent z-plasty for band release, followed by manipulation and plaster casting. The other four extremities had incomplete bands, which were initially subjected to manipulation using the Ponseti method, followed by band release at the time of the Achilles tenotomy. Results: Over a mean follow-up time of 5 years, 7 of the study feet were plantigrade and painless, with no limitations of activities of daily living; only one foot showed limited dorsiflexion, and that patient is awaiting corrective surgery. This limb showed a double band in zone 2 that was both complete and deep. Conclusion: Despite the rigidity, clubfoot secondary to amniotic band constriction syndrome showed good outcomes when treated using the Ponseti method.